Contrastive Analysis Of Various Speech Events In English and Batak Toba - Destri Yani Puspita Sari Gultom; Yohana Anggita Sidabutar; Theresa Nanda Kristina; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research to compares and contrasts by analyzing various speech events in English language and Batak toba language. To show that in English and Batak toba language there are formal and informal language differences in life. This study aims to compare how the expressions are found in English and Batak toba language. Qualitative method was used in this research. Comparing the nine expressions in English and Batak toba language, they have similarities in expression, namely in "pleasure" and the eight expressions have differences. In this paper, the main focus is highlighting the contrastive analysis of various speech acts events in English and Batak Toba with regard to range, frequency, structure, formality, and politeness